The final solution is all the values that make <span><span><span><span><span>(<span>x+4</span>)</span><span>(<span>x<span>−4</span></span>)</span></span><span>(<span><span>x2</span>+4</span>)</span></span>=0</span><span><span><span><span>x+4</span><span>x<span>-4</span></span></span><span><span>x2</span>+4</span></span>=0</span></span> true.<span>x=<span>−4</span>,4,<span>2i</span>,<span><span>−2</span><span>i</span></span></span>
Minus 64 from both sides x⁴-12x²-64=0 hmm what 2 numbers multiply to -64 and add to get -12 -16 and 4 (x²-16)(x²+4)=0 oh look a difference of 2 perfect squares (x²-4²)(x²+4)=0 (x-4)(x+4)(x²+4)=0 set each to zero
x-4=0 x=4
x+4=0 x=-4
x²+4=0 x²=-4 if you have learend complex roots then sqrt both sides to get x=-2i or 2i